Performance Analysis of Shear Wall Joint Connection in Highrise Building Using Finite Element - Sarasanty, Diah; Ali Wafa Baidowi, Ahmad (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
Multi-story buildings have a risk of structural failure, especially at joint connections, including raft elements and shear walls, due to the interaction behavior of the shear joints. The problem raised in this research is how to analyze the performance of raft foundation shear wall structural connections in high-rise buildings. The researchers started by simulating the initial model using the element method to find out the detailed capabilities of the raft foundation and shear walls and obtain values that could measure the capabilities of the substructure used. The results of this research explain the results of the evaluation of connection performance, namely, the pile raft phase with fc' 35 MPa and the shear wall phase with fc' 50 MPa. From the analysis in this research, visualization from the ABAQUS program of the force conditions acting on the connection structure was obtained, namely compression damage of 0.0021 at an ultimate compressive stress of 43 MPa and 0.0006 at an ultimate compressive stress of 57.97 MPa. We also perform analytical calculations to determine the tensile and compressive strain values. In the future, it is hoped that it will be possible to make part of the reference the use of connections with similar models and sizes at project work stages with the same characteristics as a contribution to developing building structural safety requirements.